Peningkatan Aktivitas dan Hasil Belajar Materi Tari Pendek Bertema Melalui Metode Field Trip pada Siswa Kelas II SD Negeri 010 Sei Simpang Dua - Kusrini, Sri (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aimed to improve teacher performance, student engagement, and learning outcomes in Thematic Short Dance for third-grade students at SD 010 Sei Simpang Dua. Twenty-six students from SD Negeri Kalibatur in the academic year 2021/2022 participated in the two-cycle research, involving planning, implementation, observation, and reflection. In that academic year, students' learning outcomes were hindered by a teacher-centered approach, limiting their creativity and engagement. To address this, the teacher implemented a field trip method in Thematic Short Dance. Results showed improvement from cycle I to cycle II. Average student learning outcomes increased from 75.40 to 80.65, with mastery rising from 69.23% to 88.46%. Student activity during learning also improved from 71.93% to 78.77%. Teacher performance rose from 80.42 (B) to 88.72 (A). The field trip method effectively enhanced teacher performance, student engagement, and learning outcomes. This research contributes to teaching methods in Arts and Skills (Seni Budaya dan Keterampilan - SBK) at the elementary school level.